Diabetes Mellitus Pada Petani - Fandana, Refi (Wellness And Healthy Magazine, 2020)
Diabetes mellitus is a chronic metabolic disease that still remains a significant health problem in the world. In Indonesia, 7 percent of people age more than 15 have diabetes, and it caused 99.400 deaths in 2014. There are typical symptoms such as polyuria, polyphagia, polydipsia, and weight loss, and other symptoms. Diabetes mellitus is a multifactorial disease that affected by genetic component, environment, social, and culture. One of the risk factors that effect is exposure to chemical compound for example pesticides. Pesticides are chemical compounds that are used to kill pests in various sectors of life. Agricultural culture is related to pesticides. Pesticides are potentially toxic to a human when humans are exposed to pesticides through oral, transdermal, or inhalation. The pesticides that enter the human digestive system will be converted into glucose by gluconeogenesis in the intestine and liver. Moreover, there is a relationship between work period, pesticide spraying frequency, use of personal protective equipment, and pesticide dosage with the incidence of diabetes mellitus type 2. Farmers are a higher risk of diabetes mellitus type 2.